Subjects, institutions and Human Rights training (2019)
This article identifies the position of the Ministry ofEducation and the National Police representativestowards human rights training in basic secondarypublic schools educational institutions, besideshaving adverse regional contexts. A qualitativedescriptive research with mixed methods wasdeveloped, as it involved an institutional programsdocumentary revision, as well as the application of136 open questions surveys, just as “Todos a aprender”project teachers interviews in 5 Departments. Also, 2managers and 139 students of the non-commissionedtraining school and promotions of the NationalPolice were involved. As a conclusion, there aredistances between the Police and the Ministry ofNational Education, regarding education, training,and information processes about the rights subjectas classroom teaching strategies, aiming to mitigatebehaviors that lead to future police cases. Likewise,it is observed that there is an interest in promoting astate policy through these interventions.